Systemic tuberculosis: a case during the COVID-19 pandemic - Maggi-Panato, Alessandra (2022)
A 33-year-old male patient, who was brought by his wife to the Emergency Service for changes in his behavior. He had a history of increased volume of the right knee and an ulcer in that joint. Multisystem damage was observed during hospitalization. The pathological study evidenced the presence of systemic tuberculosis, affecting the knee, lungs, brain and kidneys. With anti-tuberculosis treatment, the patient progressed rapidly towards improvement.